A new strategy based on SmRho protein loaded chitosan nanoparticles as a candidate oral vaccine against schistosomiasis. - Carolina R Oliveira; Cíntia M F Rezende; Marina R Silva; Ana Paula Pêgo; Olga Borges; Alfredo M Goes (Public Library of Science (PLoS), 2012)
BACKGROUND: Schistosomiasis is one of the most important neglected tropical diseases and an effective control is unlikely in the absence of improved sanitation and vaccination. A new approach of oral vaccination with alginate coated chitosan nanoparticles appears interesting because their great stability and the ease of target accessibility, besides of chitosan and alginate immunostimulatory properties. Here we propose a candidate vaccine based on the combination of chitosan-based nanoparticles containing the antigen SmRho and coated with sodium alginate. METHODS AND FINDINGS: Our results showed an efficient performance of protein loading of nanoparticles before and after coating with alginate. Characterization of the resulting nanoparticles reported a size around 430 nm and a negative zeta potential. In vitro release studies of protein showed great stability of coated nanoparticles in simulated gastric fluid (SGF) and simulated intestinal fluid (SIF). Further in vivo studies was performed with different formulations of chitosan nanoparticles and it showed that oral immunization was not able to induce high levels of antibodies, otherwise intramuscular immunization induced high levels of both subtypes IgG1 and IgG2a SmRho specific antibodies. Mice immunized with nanoparticles associated to CpG showed significant modulation of granuloma reaction. Mice from all groups immunized orally with nanoparticles presented significant levels of protection against infection challenge with S. mansoni worms, suggesting an important role of chitosan in inducing a protective immune response. Finally, mice immunized with nanoparticles associated with the antigen SmRho plus CpG had 38% of the granuloma area reduced and also presented 48% of protection against of S. mansoni infection. CONCLUSIONS: Taken together, this results support this new strategy as an efficient delivery system and a potential vaccine against schistosomiasis.